Field-programmable gate array-based field-oriented control for permanent magnet synchronous motor drive - Nam Duong Le; Le Quang Linh; Nguyen Tien Huy Cong; Phuong Vu; Tung Lam Nguyen (Universitas Ahmad Dahlan, 2023)
Permanent magnet synchronous motor (PMSM) is a special type of synchronous electric motor that has many applications such as in the manufacturing industry of robots, self-propelled mechanisms, in the medical fiel. In this paper, the permanent magnet synchronous motor motor control structure according to the field-oriented control (FOC) algorithm will be implemented on the field-programmable gate array (FPGA) card. Function blocks in FOC algorithm for example PI controller, space vector pulse width modulation (SVPWM) algorithm will be integrated into individual itegrated circuit (Ics) then will be connected to form an IC with the function of implementing FOC algorithm. Furthermore, this algorithm will be used for powertrains using gallium nitride (GaN). GaN technology provides switching frequencies up to 100 kHz instead of the upper 2 to 20 kHz like insulated gate bipolar transistor (IGBT) transistors. With GaN technology, it is possible to reduce switching losses as well as increase the efficiency of the power converter. The performance results will be verified through the typhoon hardware in the loop (HIL) device.